Contesting Gendered Authority in Islamic Discourse: A Comparative Discourse of Hibah Ra’ūf ‘Izzat and Siti Musdah Mulia on the Legitimacy of Women’s Leadership - Mumayyizah, Siti; Slamet Muliono Redjosari (Journal of Islamic Philosophy and Contemporary Thought, 2023)
This study critically analyzes the differences in the views of Hibah Ra’ūf ‘Izzat and Siti Musdah Mulia regarding women’s leadership from the perspective of contemporary Islamic thought. Using a qualitative method through comparative analysis of primary and secondary texts, this study examines the theological, legal, and sociopolitical dimensions that shape the argumentative framework of each figure. Both agree on the principle of gender equality but take different approaches: Ra’ūf ‘Izzat operates within the framework of normative fiqh while offering selective reinterpretations that allow women’s participation in public spaces based on competence, whereas Musdah Mulia advocates a transformative and emancipatory approach, firmly rejecting patriarchal interpretations and emphasizing the values of justice, equality, and humanity in the Quran as the basis for leadership legitimacy. The findings of this study reveal the dynamics between reformist moderation and structural criticism in contemporary Islamic studies. Its contribution lies in strengthening the discourse on women’s leadership based on Islamic spiritual ethics and modern civil rights, as well as opening up space for reflection on the role of women in the political and religious structures of the Muslim community.